Germination and initial development in vitro, and acclimatization of Oeceoclades maculata (Orchidaceae), aiming at its reintroduction in natural environments (Acta Scientiarum. Biological Sciences, 2022)
Oeceoclades maculata is a terrestrial orchid species that has potential for commercial purposes. Taking that into consideration, the present investigation aimed at studying its germination and initial development in vitro as well as its acclimatization. The influence of Murashige and Skoog (MS), Knudson C (KC), and Vacin and Went (VW) media in the presence and absence of 0.3% activated charcoal on in vitro germination and protocorm development were investigated. The effects of different concentrations of BA in combination with 0.5 mg L-1 NAA on seedling multiplication and growth were evaluated. The possibility of using dark-grown stem segments for micropropagation and acclimatization under laboratory and field conditions was also assessed. The results indicated that the most adequate media for germination were full-strength MS enriched with activated charcoal or KC supplemented with 1.5 mg L-1 BA in combination with 0.5 mg L-1 NAA. In terms of protocorm development, KC supplemented with 1.5 mg L-1 BA alone or in combination with 0.5 mg L-1 NAA provided the best results. The addition of 1.5 mg L-1 BA in combination with 0.5 mg L-1 NAA to KC medium favored the best results for seedling multiplication and development. The use of dark-grown stem segments is a viable alternative for the micropropagation of O. maculata. Regarding acclimatization, 100% survival of plants was observed during the initial phases and under field conditions average survival was 53.33%.